Cardiac Tamponade in a Patient With Hypothyroidism: A Case Report - Hermifa Dwi Aninnaimah; Sony Wibisono (Indian Journal of Forensic Medicine & Toxicology, 2022)
Cardiac tamponade as a manifestation in newly diagnosed hypothyroidism is a rare condition becausefluid accumulate slowly. We present a 38-year-old woman with massive pericardial effusion withcardiac tamponade findings in echocardiography without hemodynamic disturbance. Pericardiocentesiswas done, but pericardial effusion was not improved. Other secondary causes of pericardial effusionincluding inflammation, infection, autoimmune disease, and malignancy were ruled out. The patienthad a history of thyroidectomy 4 years prior and thyroid function test confirm the diagnosis ofhypothyroidism. The patient was given levothyroxine with initial dose of 400 mcg and continued with100 mcg daily. The pericardial effusion significantly improved in a week.